Ars2 promotes cell proliferation and tumorigenicity in glioblastoma through regulating miR-6798-3p. Issue 1 (December 2018) - Chen, Yibiao; Hu, Xiaoye; Li, Yunong; Zhang, Hongwei; Fu, Ruoqiu; Liu, Yanxia; Hu, Jinjiao; Deng, Qin; Luo, Qingsong; Zhang, Dunke; Gao, Ning; Cui, Hongjuan
Abstract Arsenic resistance protein 2 (Ars2) is a component of the nuclear RNA cap-binding complex (CBC) that is important for some microRNA biogenesis and it is critical for cell proliferation and tumorigenicity. However, mechanism of Ars2-regulated cellular proliferation and tumorigenicity in glioblastoma has not been fully understood. Western blotting was used to detect the expressions of Ars2, p53, p21, and cleavage/activation of caspases-3 (C-Caspase 3). Microarray and Quantitative Real-time PCR (qRT-PCR) were performed to identify the Ars2-regulated microRNAs. Apoptosis assessed by flow cytometry analysis was used to evaluate the role of Ars2 in cells proliferation. The lentivirus-mediated gene knockdown approach was conducted to determine the function of Ars2. The orthotopic glioblastoma xenograft was used to demonstrate the role of Ars2 in glioblastoma growthin vivo . The high expression of Ars2 was observed in several glioblastoma cell lines and was significantly associated with poorer overall survival. Importantly, the overexpression of Ars2 promoted cell proliferation and colony formation in glioblastoma cells, whereas the depletion of Ars2 inhibited cell proliferation, colony formation, and tumor growth. Mechanistic study revealed that knockdown of Ars2 reduced the expression levels of miR-6798-3p, which was responsible for the up-regulation of p53 and p21, leading to apoptosis. Furthermore, the knockdown of Ars2 suppressed tumor growth in orthotopic glioblastoma xenograft model and significantly prolonged the survival time of the tumor-bearing mice. These findings identify a critical role for Ars2 in regulation of proliferation and tumorigenicity in glioblastoma and suggest that Ars2 could be a critical therapeutic target for glioblastoma intervention.